Aggressive under certain conditions: A neo-classical realistic analysis of the development in Chinese foreign and security policy - Sørensen, Camilla T.N. (Politica, 2015)
What kind of great power is China? The increasingly prevalent argument is that China is an aggressive one. Chinese activities in the South and East China Sea are especially highlighted as examples of a generally more assertive and ambitious China. Is this the case? No. There is no clear line in or strategy behind the development in Chinese foreign and security policy. A neoclassical realist analysis shows how the ongoing developments in the overall power structure driven by an economically and militarily stronger China present a new room of maneuver for Chinese foreign and security policy and further how concerns of the Chinese leaders about securing their own domestic legitimacy then pull Chinese foreign and security policy in different directions.